MENULIS KREATIF BERBASIS BUDAYA LOKAL BAGI GURU SMPN 2 PADANG GUNA MENDUKUNG IMPLEMENTASI GERAKAN LITERASI SEKOLAH - Agus Nurofik; Nini; Tri Irfa Indrayani; Sartika Yuliana; Olinita (Bajang Institute, 2022)
The School Literacy Movement (GLS) is a government program contained in the Minister of Education and Culture Regulation Number 23 of 2015 with the aim of building a literacy culture in schools so that school residents become literate. Although it has become a national policy, not all schools have implemented the GLS as expected. SMPN 2 Padang is one of them. The problem that occurs at SMPN 2 Padang is the lack of quantity and type of reading materials and other infrastructure. This problem can be overcome by empowering teachers' writing skills. Therefore, the purpose of this community service is to provide creative writing assistance for SMPN 2 Padang teachers so that teachers can contribute reading materials to fill the gaps. The service method is carried out by collective and personal workshops and mentoring, both through face-to-face and online meetings. The targeted outputs are (a) the skills of teachers in obtaining technology-based information sources, (b) the ability of teachers to process ideas or writing themes, (c) the courage of teachers to express ideas by paying attention to linguistic aspects, (d) the ability of teachers to write ideas by paying attention to the style of the environment. , and (e) record written work with the teacher in a book. The results of the activity show that the main problem for the teacher is in exploring ideas and starting writing. Through this activity, teachers feel very helpful and motivated to optimize the implementation of GLS in schools. Teachers have been able to access various information related to cultural literacy and produce a joint work book